MODIFIKASI PERILAKU UNTUK PENGENALAN DIRI DALAM MEMBENTUK SIKAP POSITIF PESERTA DIDIK - Otih Jembarwati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
This quantitative research was conducted on students in class X of SMA GB in Semarang. Subjects were students who become the participant of lecturer’s service program. The learners undergoing training to identify themselves and carry out training for their behavioral changes. The training result data was submitted to the counselor teacher for further treatment. Learners acquired self-image regarding: resilience, the advantages and disadvantages of their self, self-description of interpersonal behavior when interacting with the teacher. At the end of the study there is increasing recognition scores of self learners. The training participants reported some commitment and plan to change of their attitude which written in students’ diary.